Retrograde Type A Aortic Dissection 48 Hours after TEVAR in a Patient with a Delayed Diagnosis of Vascular Ehlers-Danlos Syndrome - Diebels, Ian; Hendriks, Jeroen M.H.; Durnez, Joke; Paelinck, Bernard P.; El Addouli, Haroun; Laga, Steven; Loeys, Bart L. (AORTA, 2022)
We report a case of a fatal retrograde Type A aortic dissection following thoracic endovascular aortic repair (TEVAR). The patient was diagnosed with vascular Ehlers-Danlos syndrome (vEDS) only postoperatively, which is a relative contraindication for TEVAR. The patient had no major or minor criteria for vEDS. This case report emphasizes pitfalls of TEVAR in patients with a connective tissue disorder.
Keywords: acute aortic syndrome; aortic dissection; thoracic endovascular aortic repair; vascular Ehlers-Danlos syndrome; connective tissue disorder